2016
DOI: 10.1007/s10103-016-2001-0
|View full text |Cite|
|
Sign up to set email alerts
|

Picosecond lasers for tattoo removal: a systematic review

Abstract: Given that the pigment particles in tattoos have a relaxation time of <10 ns, picosecond lasers would be expected to be more effective than nanosecond lasers in tattoo removal. To systematically review the evidence regarding the effectiveness and safety of picosecond lasers for tattoo removal, Pubmed, Cochrane Central Register of Controlled Trials (CENTRAL), ClinicalTrials.gov, and reference lists were searched for relevant trials. The primary outcome was >70 % clearance of tattoo pigment. Secondary outcomes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
37
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 31 publications
1
37
0
7
Order By: Relevance
“…The commonly used pulse lasers for tattoo removal are Qswitched lasers producing nanosecond (ns) pulse durations of approximately 5 -100 ns at various wavelengths such as ruby (694 nm), alexandrite (755 nm), and Nd:YAG (532 nm and 1064 nm) lasers. Picosecond (ps) pulse lasers, which have shorter pulse durations of 350 -750 ps, have been developed recently [1][2][3][4][5]. The logic is that ns pulse duration might be too long for effective photothermolysis of small tattoo particles having thermal relaxation time (TRT) in ps ranges.…”
Section: Introductionmentioning
confidence: 99%
“…The commonly used pulse lasers for tattoo removal are Qswitched lasers producing nanosecond (ns) pulse durations of approximately 5 -100 ns at various wavelengths such as ruby (694 nm), alexandrite (755 nm), and Nd:YAG (532 nm and 1064 nm) lasers. Picosecond (ps) pulse lasers, which have shorter pulse durations of 350 -750 ps, have been developed recently [1][2][3][4][5]. The logic is that ns pulse duration might be too long for effective photothermolysis of small tattoo particles having thermal relaxation time (TRT) in ps ranges.…”
Section: Introductionmentioning
confidence: 99%
“…Dies ist der Ansatzpunkt, da aus technischer Sicht die derzeitigen Geräte nicht im Pikosekundenbereich, sondern im Sub-Nanosekundenbereich arbeiten. Inzwischen hält diese Erkenntnis immer mehr Einzug in Patientenforen [6], aber auch unter Laserdermatologen [7]. Das Ergebnis unserer randomisierten kontrollierten Studie, in der wir einfarbige schwarze Tattoos behandelten, zeigte dies zu unserer eigenen Überraschung deutlich [5].…”
Section: Clinical Letterunclassified
“…Since most tattoo particles' size are approximately 100 nm, corresponding to a thermal relaxation time of less than 10 ns, picosecond (PS) lasers could be more effective than QS lasers, theoretically. Clinical trials have reported the efficacy and safety of PS lasers in the treatment of multicolored and recalcitrant tattoos [3] .…”
mentioning
confidence: 99%
“…The ability of PS lasers to remove multicolored tattoos was shown for green, yellow, red, and purple tattoos. However, the findings was not directly compared with the results of the traditional QS lasers [3] .…”
mentioning
confidence: 99%